2018
DOI: 10.1051/shsconf/20184801023
|View full text |Cite
|
Sign up to set email alerts
|

Environment from a different perspective: Analysing the environmental problem awareness of undergraduates

Abstract: The study aims to analyse the awareness levels of university students towards the environmental problems in terms of the variables of faculty and gender. The study was conducted with 149 undergraduate students from the faculty of engineering, health sciences and educational sciences in North Cyprus. The research conducted with survey study and identified the awareness levels of students towards environmental problems through “Environmental Problems Awareness Scale”, developed by Güven and Aydoǧdu [1] in consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…The results showed that the respondents who were studying science-related subjects had more knowledge about e-waste when compared to the students in other streams of education. This study agrees with other studies that have shown that the respondents from the science background are more knowledgeable about the environment, and also, the awareness of females about the environment is greater when compared to males [27,68]. The findings of the study suggest that age and knowledge about e-waste are related.…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that the respondents who were studying science-related subjects had more knowledge about e-waste when compared to the students in other streams of education. This study agrees with other studies that have shown that the respondents from the science background are more knowledgeable about the environment, and also, the awareness of females about the environment is greater when compared to males [27,68]. The findings of the study suggest that age and knowledge about e-waste are related.…”
Section: Discussionsupporting
confidence: 91%